Empirical study on the culture of successful knowledge creation and knowledge sharing in institute of higher learning (IHL) - Ab Aziz, Nur Faizah; Ahmad Lotfi, Nurul A'tiyah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
The culture of knowledge creation and knowledge sharing play very important role in the successful implementation of Knowledge Management in any Public or Private Institution of Higher Learning. The purpose of this study is to see how the culture of Knowledge Creation (KC) and Knowledge Sharing (KS) is applied in Public or Private Universities in Malaysia. A survey was designed and conducted with students Academician in the universities in Malaysia. Survey questions designed to examine perceptions of all variables were identified. Data from 17 respondents were used to validate the hypotheses. The results of the study show that the individual culture and top management’s support are important which it will be influencing the knowledge sharing behavior in the institutions.